IOT-ENABLED INTERACTIVE VISUAL ART DISPLAYS THAT RESPOND TO ENVIRONMENTAL CHANGES DYNAMICALLY - Dash, Ipsita; Panneerselvam, Ponmurugan; Sudan, Prerak; Chavan, Gajanan; Arumugam, Suresh; Boregowda, Vinay Kumar Sadolalu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The adoption of Internet of Things (IoT) technologies and integration with the field of digital visual arts has made possible the creation of interactive art systems, which are responsive to the conditions in the environment. The paper presents the design and deployment of interactive visual art displays mounted in the form of the IoT which can adjust their visual representations, in real time, as a response to environmental data. The given system consists of several environmental sensors such as temperature, the intensity of lights, humidity, sound level, and movement detection that are connected using IoT sensor networks and microcontrollers processing units. These sensors continuously scan environmental information that are sent to a data processing unit, where decision logic algorithms are used to process the information and as such cause digital display interfaces to undergo respective types of visual changes. The conceptual model integrates hardware elements like sensors, microcontrollers and display systems with software systems that are built on dynamic visual representation and data centric interaction. By so integrating together, environmental variation affects other parameters of art, like color intensity, motion pattern, brightness, and visual composition. The paper outlines how IoT technologies can improve the level of audience engagement by changing the passive art displays into immersive and interactive activities.